Splenic abscess in an adult patient. A case Report - Mayquel Monzón Rodríguez; Amanda Rodríguez Chaviano; Joel David Monzón Li (Medisur)
The splenic abscess is a rare entity. It is defined as the presence of a space-occupying lesion in the spleen associated with infection. It has been described in 0.14-0.7% of autopsy studies. The case of a 60-years-old patient, white-skinned, who came to the hospital due to fever and diarrhea, with pain in the left lumbar fossa is presented. He was admitted and transferred to the Intensive Care Unit due to acute renal failure due to dehydration. When transferred to the open room, a splenic abscess was diagnosed by ultrasound and tomography. It was not decided to operate at that time because there are no criteria. Subsequently, he presented acute abdomen and septic shock due to rupture of the abscess into the abdominal cavity and underwent emergency surgery, performing splenectomy and the cavity’s toilette. His subsequent evolution was positive. Due to the unusual nature of this entity, it was decided to publish the case.